Meningkatkan Kemampuan Menulis Huruf Vokal (a, i, u, e, o) Melalui Metode VAKT bagi Anak Tunagrahita Sedang di SLB Talawi Sawahlunto - Desi Kumilasari; Mega Iswari; Ganda Sumekar (Universitas Negeri Padang, 2018)
This research of background overshadow by problems which researcher find in SLB Talawi Sawahlunto, a child of tunagrahita semester II finding difficulties in lettering vowel (a,i,u,e,o). Matter is proven, when done/conducted by observation in the reality child unable to letter. To overcome this problems [of] researcher try to give alternative by using method of VAKT assumed can assist tunagrahita in improve;repairing ability letter. This research aim to to increase ability letter vowel (a,i,u,e,o) in SLB Talawi Sawahlunto. Type Research is Single Subject Research (SSR) that is research which [in] [doing/conducting] in a condition differ to use A-B desain. where condition of baseline namely the condition of early ability of child in lettering vowel before giving action. While condition of B represent the condition of intervention namely the condition of where child giving intervention [pass/through] method of VAKT. Size measure Goals of behavior seen from how much/many [gratuity/ %] of child can letter from given vowel (a,i,u,e,o). Result of this research seen that ability letter child vowel of tungrahita is mount after giving method of VAKT. This Matter of terbuktu when perception performed within two session that is is first session of baseline before given by intervention which the five of perception times;rill, and percentage of ability letter this condition lay in to span 6,66%, 6,66%, 6,66%, 6,66% and 6,66%. Intervention Kedua,sesi (B) by using method of VAKT, perception counted nine times perception, and percentage of ability letter child vowel of tunagrahita [at] this condition lay in to span 6,66%, 33,3%, 60%, 66,6%, 80%, 73,3%, 86,6%, 100%, 100%. Pursuant to result of this research can mean that ability letter child vowel of tunagrahita in SLB Talawi Sawahlunto can mount to method of VAKT as well as can be suggested to teacher, headmaster that method of VAKT can be used as media in improving ability write child of tunagrahita.